Multiferroics: Multiferroic Clusters: A New Perspective for Relaxor‐Type Room‐Temperature Multiferroics (Adv. Funct. Mater. 13/2016). (April 2016) - Henrichs, Leonard F.; Cespedes, Oscar; Bennett, James; Landers, Joachim; Salamon, Soma; Heuser, Christian; Hansen, Thomas; Helbig, Tim; Gutfleisch, Oliver; Lupascu, Doru C.; Wende, Heiko; Kleemann, Wolfgang; et al.
Abstract : L. F. Henrichs and co‐workers report on page 2111 an electric‐field‐induced magnetoelectric switching in (BiFe0.9 Co0.1 O3 )0.4 –(Bi1/2 K1/2 TiO3 )0.6 ceramics, within newly discovered multiferroic clusters (MFCs). The MFCs are suggested to be both ferroelectric and ferromagnetic, and ferromagnetic ordering leads to an exceptionally large Néel temperature. The material has potential for applications in sensors and memory devices.